55.4k views
5 votes
-3 ≤ k/2; k=-2
show your work

User Mike Cluck
by
5.2k points

2 Answers

4 votes
Let's solve your inequality step-by-step.
−3 ≤ k/2
Step 1: Simplify both sides of the inequality.
− 3 ≤ 1/2k
Step 2: Flip the equation.
12k ≤-3
Step 3: Multiply both sides by 2.
2*(12k) ≥ (2)*(−3)
Answer:
k ≥ − 6
You can search up ‘mathpapa’ its a Calculator.

User Zac Smith
by
5.0k points
4 votes
Divide -2 by 2.
3 ≤ −1
User August Flanagan
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.